Perencanaan Pembelajaran Berbasis Kurikulum di MAN 1 Kota Padang - Rahma Muthia Febriliana; Nita Putri Utami (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the curriculum-based learning planning at MAN 1 Kota Padang, focusing on the teaching materials used in grades X and XI (Merdeka Curriculum) as well as grade XII (2013 Curriculum). The approach used is descriptive qualitative with research instruments including interview guidelines and observation sheets. Data collection techniques include in-depth interviews, direct observations, and documentation. The research results show that the teaching materials are developed collaboratively through KKG forums and have been adjusted to the academic calendar from the Ministry of Religion. There are differences in the approach to developing teaching materials between the Merdeka Curriculum and the 2013 Curriculum, both in structure and flexibility. In general, teachers have been able to adapt the teaching materials to the needs of students, although there are still obstacles such as time constraints and variations in student abilities. Thus it can be concluded that the learning planning is very effective, namely 84.35%. Therefore, further training is needed to improve the quality of curriculum-based learning planning.